2012
DOI: 10.1074/jbc.m111.326074
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 Promotes Both Caspase-dependent and Caspase-independent Apoptotic Cell Death via the Calpain/Bax Protein Signaling Pathway

Abstract: Background: The function of transglutaminase 2 (TG2) in dying cells is ambiguous. Results: TG2 activity facilitates simultaneous caspase-dependent and apoptosis-inducing factor-mediated apoptotic cell death via a calpain/Bax signaling pathway. Conclusion: We demonstrated a new mechanism of apoptotic cell death induced by photodynamic therapy (PDT). Significance: Understanding the function of TG2 as a therapeutic target will contribute to improved cancer treatments using PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
2
29
0
1
Order By: Relevance
“…50,51 Our results were in agreement with those from previous studies. We also observed that the translocation of Bax and cytochrome C were blocked by NAC following PDT treatment (Figure 7), which might be because ROS bursts following PDT play an important role in regulating the translocation and cytochrome C. 52 Our findings demonstrated that UCNPs-Ce6-mediated PDT induces apoptosis in THP-1 macrophages via the mitochondrial caspase pathway, which is activated by ROS bursts following PDT treatment (Figure 8). …”
mentioning
confidence: 53%
“…50,51 Our results were in agreement with those from previous studies. We also observed that the translocation of Bax and cytochrome C were blocked by NAC following PDT treatment (Figure 7), which might be because ROS bursts following PDT play an important role in regulating the translocation and cytochrome C. 52 Our findings demonstrated that UCNPs-Ce6-mediated PDT induces apoptosis in THP-1 macrophages via the mitochondrial caspase pathway, which is activated by ROS bursts following PDT treatment (Figure 8). …”
mentioning
confidence: 53%
“…Anticancer drugs may induce mitochondrial dysfunction in cells via dissipation of ΔΨm leading to liberation of numerous cell death proteins from the mitochondria (24). Therefore, it was reported that the intrinsic pathway depends on the dysfunction of the mitochondria resulting from an increase in the ratio of Bak:Bcl-2 which is caused by anticancer drugs thus leading to AIF and Endo G release from the mitochondria before inducing apoptosis (25)(26)(27) which is termed caspase-independent pathways or alternatively causing cytochrome c release, activation of caspase-9 and -3 resulting in apoptosis termed the caspase-dependent pathway (28). Our results showed that DMC induced mitochondrial dysfunction (decreased levels of ΔΨm) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It should be interesting that cystamine attenuated not only TG2 activity but also TG2 expression, which were induced by OGD. Although cystamine is a transglutaminase inhibitor and its underlying mechanism remains unknown, previous reports also demonstrated the suppression of TG2 expression by cystamine (31,32). Then by using TG2-specific inhibitor R283 and TG2-specific siRNA, we attempted to confirm whether or not TG2 is involved in suppression of PAC1 in OGD-induced ER stress.…”
Section: Discussionmentioning
confidence: 96%